Evaluation of Agricultural Waste Utilization as Alternative Feed to Improve Beef Cattle Productivity - Kadek Ayu Kurnia; Silvia Grossi (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The increasing demand for beef production requires innovative strategies to maintain productivity while reducing feed costs and environmental impacts. One promising approach involves the utilization of agricultural waste as an alternative feed resource for beef cattle. This study evaluates the effectiveness of agricultural waste utilization in improving beef cattle productivity through a systematic literature-based analysis of empirical studies. Data were collected from peer-reviewed journal articles, conference proceedings, and scientific reports published between 1999 and 2025. The analysis focuses on feed efficiency, animal growth performance, and economic feasibility. The results indicate that various agricultural by-products, including crop residues, agro-industrial waste, and food waste biomass, can enhance feed utilization and growth performance when properly processed and balanced nutritionally. Studies demonstrate that feed formulations containing agricultural waste significantly improve average daily gain, rumen function, and feed conversion ratios in beef cattle. In addition, agricultural waste-based feed contributes to sustainable livestock production by reducing feed costs and minimizing environmental waste. However, nutritional variability and digestibility remain challenges that require proper treatment and supplementation. This study concludes that agricultural waste represents a viable and sustainable alternative feed resource for improving beef cattle productivity, especially in regions with abundant agricultural residues. Further research should focus on optimizing processing technologies and nutrient balancing to maximize livestock performance.